Faculty perceptions, awareness and use of open educational resources for teaching and learning in higher education: a cross-comparative analysis - Marin, Victoria; Zawacki-Richter, Olaf; Aydin, Cengiz H.; Bedenlier, Svenja; Bond, Melissa; Bozkurt, Aras; Conrad, Dianne; Jung, Insung; Kondakci, Yasar; Prinsloo, Paul; Roberts, Jennifer; Veletsianos, George; et al. (Research and Practice in Technology Enhanced Learning, 2022)
This paper explores faculty's perspectives and use of open educational resources (OER) and their repositories across different countries by conducting a multiple case study to find similarities and differences between academics' awareness, perceptions and use of OER, as well as examining related aspects of institutional policy and quality that may influence individual views. Data were collected through nine expert reports on each country studied (Australia, Canada, China, Germany, Japan, South Africa, South Korea, Spain and Turkey) and were analyzed through qualitative content analysis using thematic coding. Findings show the impact on individual OER adoption with regard to the individual control of diverse factors by faculty members; of institutional policies and quality measures on the externally determined factors (by the institution); and of institutional professional development and provision of incentives in more internally determined factors (by the faculty members themselves). These findings carry implications for higher education institutions around the world in their attempt to boost OER adoption by faculty members.
CRIS-Team WoS Importer:2022-04-08
Keywords: Open educational resources (OER); Repositories; Higher education (HE); Faculty members; International comparison